PARASITE COMMUNITIES OF PATAGONOTOTHEN TESSELLATA (RICHARDSON, 1845) (PISCES: NOTOTHENIIDAE) OF AUSTRAL CHILE: HOW DETERMINANT IS THE HOST SEX? - Cortés, Catalina (2021)
The knowledge of the parasites community in marine fish is extensive. However, there is scarce information about their parasites in several fish species, such as the case of Patagonotothen tessellate (Richardson, 1845), which is a fish widely distributed and abundant on the Patagonia. The aim of this study was to determinate the community composition of parasites in P. tessellata and to establish the role of the host sex in the composition of parasites through population and community descriptors of parasites. In January 2018, 118 specimens of P. tessellata were collected from two nearby locations, Prat bay and Remota bay, Puerto Natales, Austral Chile. From the fish sample, 13 parasite species were recovered, mostly from the Phyla Nematoda and Acanthocephala. As a result, the nematode Pseudodelphis sp. followed by the acanthocephalan Hypoechinorhynchus magellanicus (Szidat, 1950) were those with the highest prevalence (78,8% y 53,4% respectively) and abundance (7,18 ± 17,95 y 7,30 ± 15,21 respectively). Male and female hosts had similar body sizes and positive correlation between weight-length, also, no significant differences were observed in the composition and parasite load. Besides, there is no connection between the fish sex and its parasitic composition, because there were no significant differences in the prevalence or in the average abundance of the parasite species between the sexes of the host. These results indicate that males and females of P. tessellata share the same habitats and have the same diet, therefore, the fishes are exposed to the same parasitic species and in the same environmental conditions.